Interfaces entre lazer e turismo em teses e dissertações brasileiras: estado do conhecimento (2009-2015) - Tatiana Neri de Aguiar dos Santos (2016)
This research is characterized as a state of knowledge and investigates the interface leisure/tourism in doctoral dissertations and masters thesis completed between 2009 and 2015 in Brazil. Its general aim is to understand the conceptions of leisure and tourism and the interfaces constituted between them in these academic works. The methodological approach is based on literature review and content analysis and takes epistemology as critique of knowledge. Following previously established methodological criteria, 15 works from different graduate programs were selected: Business Management; Architecture and Urbanism; Development and Environment; Leisure Studies; Geography; Human Geography; History, Politics and Cultural Goods; Hospitality; Urban and Regional Planning; and Tourism. The results show that leisure and tourism are understood as sociocultural phenomena but, above all, as business. The interfaces between these two subjects show that they are overlapped, with tourism standing out as a leisure option. The analyses indicate that the prioritized discussions in the selected academic works are not enough to understand the dynamics of these phenomena in different realities.